2013
DOI: 10.2147/tcrm.s52009
|View full text |Cite
|
Sign up to set email alerts
|

Treatment approaches and antibiotic use for emergency dental treatment in Turkey

Abstract: The purpose of this study was to gather information about Turkish general dental practitioners’ treatment approaches towards endodontic emergencies, antibiotic-prescribing habits, and their participation in lifelong learning programs. Questionnaires were given to dentists who attended the 16th National Congress organized by the Turkish Dental Association. From 1,400 questionnaires distributed, 589 (43%) were deemed usable in this study. This survey dealt with questions that were subdivided into two main topics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 25 publications
1
10
1
Order By: Relevance
“…For most patients were prescribed antibiotics and analgesics, especially in cases of acute apical abscesses, and only analgesics in cases of irreversible pulpitis. The study by Kaptan et al [30] reported antibiotics prescription rates of 21.7% and 41% in cases of acute apical periodontitis and acute apical abscesses, respectively, thus differing from our results. Another more recent study found that 83.9% of the patients attending an emergency department of a dental school in Brazil had no systemic drug prescribed after treatment [18].…”
Section: Discussioncontrasting
confidence: 99%
“…For most patients were prescribed antibiotics and analgesics, especially in cases of acute apical abscesses, and only analgesics in cases of irreversible pulpitis. The study by Kaptan et al [30] reported antibiotics prescription rates of 21.7% and 41% in cases of acute apical periodontitis and acute apical abscesses, respectively, thus differing from our results. Another more recent study found that 83.9% of the patients attending an emergency department of a dental school in Brazil had no systemic drug prescribed after treatment [18].…”
Section: Discussioncontrasting
confidence: 99%
“…Regarding the antibiotics prescribed to the patients included in the present study, it can be seen that more than half of the patients received amoxicillin treatment with or without beta-lactamase inhibitors. The majority of the patients took the antibiotic without beta-lactamase inhibitors, which is contrary to literature studies, which show that the main antibiotic administered for odontogenic infections is amoxicillin with beta-lactamase inhibitors [ 3 ]. The administration of an effective antibiotic in odontogenic infections is particularly important in the attempt to limit the septic process.…”
Section: Discussionmentioning
confidence: 76%
“…However, the last 10–15 years have witnessed a rebound of severe odontogenic infections caused by highly aggressive antibiotic-resistant bacteria [ 2 ]. The main cause indicated by the literature for the development of bacteria resistant to antibiotic therapy is the incorrect or inefficient administration of antibiotics [ 3 ]. Currently, a number of antibiotics for inflammatory dental pulp disorders or established abscesses are administered.…”
Section: Background and Aimsmentioning
confidence: 99%
“…Surveys carried out in other European countries ( 11 , 12 , 14 , 27 , 28 ) also found amoxicillin as the first choice antibiotic selected by dentists for the treatment of apical periodontitis. Amoxicillin is a good antibiotic for pulp-periapical disease because its great antimicrobial activity against the microbiota responsible of these pathologies.…”
Section: Discussionmentioning
confidence: 95%